Southeast Asian waxy maize (Zea mays L.), a resource for amylopectin starch quality types?. Issue 5 (21st April 2016) - Stamp, Peter; Eicke, Simona; Jampatong, Sansern; Le-Huy, Ham; Jompuk, Choosak; Escher, Felix; Streb, Sebastian
Abstract: Amylose-free ( waxy ) maize has been a vegetable (cooked ears) and staple food in Southeast Asia for centuries, resulting in hundreds of landraces (LRs) across the region. The recessive waxy allele induces soft grains with preferred cooking and flavour properties. We hypothesized that eating preferences resulted in the additional selection for different starch properties, reflected in altered starch granule morphology or amylopectin structure. A total of 41 LRs were available as starting material that had been used by different ethnic groups in Vietnam and Thailand. Unluckily, some LR were not pure waxy, but we successfully regained the original pure waxy status for most. Twenty LR were chosen for analysis of starch traits according to their purity. Four different waxy mutations were identified, including two unknown alleles. This is a strong proof for parallel independent selection of waxy maize in the region. Starch granule morphology and size were similar among all LRs. Gelatinization properties differed only between waxy and wild-type LR, and all waxy LR were comparable to a commercial waxy hybrid. The fine structure of waxy amylopectin had fewer short chains compared with that in wild-type. So far, the differences observed in starch properties are likely associated exclusively with the waxy trait. Despite the strong selection for amylose-free starch, there was no evidence for additional region wide selection for other special starch properties in our collection. In conclusion, all analyses did not encourage further targeted research on allelic variation of other starch metabolism genes for future use in the food and feed industry.